A corpus-based study of semantic neology of the covid-19 pandemic - Irene Renau (Quaderns de Filologia: Estudis Lingüístics)
Detection of semantic neology, or the emergence of new meanings in existing words, is a challenging task because it is not related to formal changes as in formal neology. In this paper, we make a series of studies to detect semantic neology in Spanish nouns in 2022, a year in which covid-19 pandemic still existed, but also other important global events, such as the Ukraine war, or economic inflation. We compare a corpus of texts from 2022 to a pre-pandemic corpus, considering changes in collocations of the target nouns. We use some statistic parameters for collocations analysis, in combination with manual analysis. Results indicate that combining key words with topic-related contexts give the best results to detect semantic neology with semi-automatic methods.